A comprehensive review of antimalarial medicinal plants used by Tanzanians - David Sylvester Kacholi (Taylor & Francis Group, 2024)
AbstractContext Tanzania has rich medicinal plant (MP) resources, and most rural inhabitants rely on traditional healing practices for their primary healthcare needs. However, available research evidence on antimalarial MPs is highly fragmented in the country.Objective This systematic review compiles ethnomedicinal research evidence on MPs used by Tanzanians as antimalarials.Materials and methods A systematic web search was conducted using various electronic databases and grey materials to gather relevant information on antimalarial MPs utilized by Tanzanians. The review was per the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement. The data were collected from 25 articles, and MS Excel software was used to analyse relevant ethnobotanical information using descriptive statistics.Results A total of 227 MPs belonging to 67 botanical families and 180 genera were identified. Fabaceae (15.9%) is the most frequently utilized family. The ethnobotanical recipes analysis indicated leaves (40%) and trees (44%) are the preferred MPs part and life form, respectively. Decoctions (67%) are the dominant preparation method of remedies. Of the recorded MPs, 25.9% have been scientifically investigated for antimalarial activities with positive results. However, 74.1% of MPs have no scientific records on antimalarial activities, but they could be potential sources of remedies.Conclusions The study discloses a wealth of antimalarial MPs possessed by Tanzanians and suggests a need for research to authenticate the healing potential of antimalarial compounds from the unstudied MPs. Additionally, it indicates that some of the presented MPs are potential sources for developing safe, effective and affordable antimalarial drugs.